Determinants of client satisfaction with family planning services in public health facilities of Jigjiga town, Eastern Ethiopia - Aregawi Gebreyesus (BMC, 2019)
Abstract Background Client satisfaction is the best indicator of quality service provision and has been found to correlate with continuity of care perceived by the client. The measurement of client satisfaction helps in understanding willingness and decisions to return for future services. Thus, this study aimed at assessing the level and factors associated with client satisfaction of FP services among family planning users. Methods An institutional based cross-sectional study was conducted on 492 family planning users in Public health facilities of Jigjiga town, Eastern Ethiopia from February 10 to March 10, 2017. Participants were chosen by systematic random sampling and interviewed immediately after having received family planning service using via a structured and pre-tested questionnaire. The data were entered into Epi Info 7 and then exported to SPSS 20 for analysis. All associations with client satisfaction were tested for statistical significance with alpha set at the 0.05 level. Result The findings of this study showed that the overall client satisfaction with FP services among FP users of public health facilities of Jigjiga town was 41.7% with 95% CI of (37 − 46.1%). Knowledge on FP [adjusted odds ratio, AOR (95% CI) = 0.037 (0.019-0.072)], demonstrate how to use the method [AOR (95% CI) = 16.1 (8.4-30.7)], describing side effect of the method [AOR (95% CI) = 2.4 (1.41-4.23)] and distance of FP user's home to health facility [AOR (95% CI) = 0.24 (0.14-0.42)] were found to be significantly associated with the client satisfaction of FP services. Conclusions The overall client satisfaction with FP services was relatively low. Knowledge of FP, demonstrating how to use the method, describing the side effect of the method and distance of FP user's home to health facilities were found to be factors that influence client satisfaction with family planning services. Thus, efforts should be made to improve on client interaction especially on the information given and knowledge of clients.